The Structure, Conduct, and Performance of the Midstream Segments of the Aquaculture Value Chain in Bangladesh - Ali, Hazrat; Belton, Ben; Khondker, Murshed-E-Jahan; Hernández, Ricardo; Haque, Mohammad Mahfujul (WorldFish, 2022)
Abstract accepted for presentation at the Annual Meeting of the World Aquaculture Society held in Singapore on 29 November to 2 December 2022. The presentation discussed the comprehensive statistically representative study of 329 aquatic product traders in 31 markets from seven districts in south and southwest Bangladesh between January and May 2021to look into the organization and behavior of actors in these segments of the aquaculture value chain in Bangladesh.